Sistematización del departamento de colecturía y su incidencia en la eficiencia del departamento de - Alvear Carpio, Rene Patricio (2017)
The Bilingual Private Educational Center "FEDERICO FROEBEL" is a private company dedicated to providing pre-school education, basic and superior to children and young people, started his work as an Educational Company in the city of Babahoyo, capital of the province of Los Rios, in 1993, by Ministerial Resolution # 33 of March 10, 1993, granted by the Provincial Directorate of Education of Los Ríos.